Facile Synthesis and Biological Evaluation of New Thieno[2, 3‐g]indolizine Derivatives. Issue 35 (15th September 2020) - Zinoveva, Anna D.; Borisova, Tatiana N.; Politova, Polina A.; Titov, Alexander A.; Varlamov, Alexey V.; Voskressensky, Leonid G.; Nguyen, Van Tuyen; Le, Tuan Anh
Abstract: An effective approach to the synthesis of thieno[2, 3‐ g ]indolizine derivatives has been developed. A wide variety of reagents such as unsaturated aldehydes, methylvinylketone, esters of acrylic acid, maleic anhydride, methyl propiolate, dimethyl and diethyl acetylenedicarboxylates in the construction of functionally diverse rarely encountered tricyclic system has been used. A high number of structurally various thieno[2, 3‐g]indolizines has been obtained in domino reactions with medium and high yields, the influence of solvents on the course of transformations has been studied, and the presence of moderate cytotoxic activity for a number of compounds has been established. Abstract : A series of novel thieno[2, 3‐ g ]indolizine derivatives have been prepared via domino‐reactions of 4‐aroyl‐6, 7‐dihydrothieno[3, 2‐c]pyridines with electron deficient alkenes and alkynes containing a carbonyl group. Developed method is a simple and convenient procedure giving good and excellent yields, completed in short reaction times, and showing a wide functional group tolerance. The in vitro biological activity of title compounds has been studied.